1990
DOI: 10.1084/jem.172.4.1025
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of experimental allergic encephalomyelitis in Lewis rats after elimination of macrophages.

Abstract: SummaryAlmost 50% of the cells infiltrating the central nervous system (CNS) of animals with experimental allergic encephalomyelitis (EAE) are macrophages (M(p) . To investigate the role of the M(p in the pathogenesis of EAE, we eliminated Mcp by means of mannosylated liposomes containing dichloromethylene diphosphonate (C12MDP) . C12MDP-containing liposomes injected intravenously eliminate M(p in spleen and liver. Incorporation of mannose into the lipid layers enables the liposomes to pass the blood-brain bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
257
1
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(273 citation statements)
references
References 41 publications
12
257
1
3
Order By: Relevance
“…The capacity of this diphosphonate drug incorporated in liposomes to deplete resident macrophages and monocytes in rats is well established [42,43]. Depletion of macrophages by this method has been used in vivo to determine the role of macrophages in EAE [44] and arthritis [45].…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of this diphosphonate drug incorporated in liposomes to deplete resident macrophages and monocytes in rats is well established [42,43]. Depletion of macrophages by this method has been used in vivo to determine the role of macrophages in EAE [44] and arthritis [45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that partial depletion of macrophages delayed the onset of clinical signs and reduced the severity of disease (20) and near complete depletion of macrophages strongly suppressed clinical symptoms of EAE (21). We have shown that many of the macrophage functions shown to contribute to EAE disease progression are regulated by FABPs.…”
mentioning
confidence: 87%
“…Much of the uncertainty arises from depletion studies, from which it seems that demyelination is not complete in the absence of microglia/macrophages (Brosnan et al, 1981;Huitinga et al, 1990). In contrast, remyelination is also seriously delayed and affected when microglia/macrophages are not present (Kotter et al, 2005;Li et al, 2005).…”
Section: Introductionmentioning
confidence: 99%